Projects for a healthy planet simple environmental experiments for kids - Levine, Shar 1953-; Chui, Terry; Grafton, Allison (New York Wiley, 1992)
Projects designed to help us understand causes of pollution, to protect our resources, and to create environmentally friendly products.
Keywords: Environmental protection -- Juvenile literature; Environmental protection -- Experiments -- Juvenile literature; Environmental protection -- Experiments; Experiments